Análise da aplicabilidade dos biopolímeros para o melhoramento da qualidade de vida Frente às possibilidades de aplicação e inovação - Rolim, David Matheus de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
Biopolymers became the target of increased attention as the need for environmentally-friendly products increased, as the use of petrochemical polymers with their non-biodegradable characteristics, leading to serious environmental problems such as the accumulation of plastics, and long-term impaing the quality of life. This work presents an analysis about the applicability of biopolymers that can benefit and provide quality of life for end users. The study was conducted through exploratory and descriptive research, seeking articles and/or books in academic data sources. In this, technological solutions are in development with this purpose, with natural polymers of different groups and their respective constituents, each one with its forms of application that can benefit the human life directly or indirectly, depending on its form of application. With these advances in technology and worldwide demand for health improvement, the substitution of non-renewable polymers with environmentally friendly materials has been tested in a number of areas for this purpose, such as biomedical, water and industrial effluent treatment, pharmacology and the generation of electricity, showing good characteristics when applied in these segments that benefit human life.
Analysis of the applicability of biopolymers to improve the quality of life In view of the possibilities of application and innovation
Monografia
Keywords: Biopolímeros; Avanço tecnológico; Saúde; Bem-estar; Biopolymers; Technological progress; Health; Welfare; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA